PRELIMINARY FINDINGS ON THE EFFECT OF Trichoderma harzianum ON THE CANNABINOIDS PRODUCTION IN MEDICINAL Cannabis sativa CLONES. - Cecilia Monaco; Marina Stocco; Jorgelina Rolleri; Axel Voisin; Christian Weber (Agricultura, 2025)
Cannabis (Cannabis sativa) is an annual plant that is widely cultivated because of its industrial and medicinal importance. An experiment was carried out in 30 liter pots. in a greenhouse with controlled conditions. Two different strains of Trichoderma harzianum (Th118 y Th 5cc) were investigated in a pot trial on agronomic and quality characteristics of clones of a variety of cannabis (Cannabis sativa L., Var. Nother light).  In this sense, the ultimate goal of this study is to shed light on the effect of T. harzianum on the root growth, vegetative development and CBD concentration and the ratio of CBD to THC.   The incorporation of T. harzianum (Th118 and Th 5cc) did not improve the growth parameters of the Cannabis plants.  No significant differences were observed between treatments for any of the parameters evaluated, under the conditions of this assay. T. harzianum ( Th118) strain, applied to the cannabis plant in two irrigations, showed the lowest values of the THC/CBD ratio (0.025). Anyway, further studies are necessary to verify whether Trichoderma spp. has the potential for implementation of medicinal cannabis production.